2021
DOI: 10.1021/acsaem.0c03127
|View full text |Cite
|
Sign up to set email alerts
|

Crystalline Disorder, Surface Chemistry, and Their Effects on the Oxygen Evolution Reaction (OER) Activity of Mass-Produced Nanostructured Iridium Oxides

Abstract: In the present study, three mass-produced commercial IrO x samples from different suppliers were studied to establish correlations between various properties and their OER activities. The structures of the electrocatalysts at different scales were explored through laboratory instrumentation, powder X-ray diffraction, and synchrotron-based X-ray total scattering experiments combined with pair distribution function analysis. X-ray photoelectron spectroscopy and energy-dispersive X-ray spectroscopy using a trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Amorphous iridium oxides are regarded as more active but less stable catalysts for the acidic OER compared with crystalline rutile-phase iridium oxides. , Several methods have been developed to obtain amorphous iridium catalysts such as surface oxidation of iridium metal, , leaching of ions in iridium compounds such as SrIrO 3 , , incorporation of alkali metal ions into iridium oxide, light-driven decomposition, and anodic deposition from iridium-based organometallic precursors. The origin of the higher electrochemical activity of amorphous iridium oxides is attributed to several possible structural features, including electronic defects (O 2p hole states), flexible and disordered [IrO 6 ] octahedrons, cross-linked hollandite-like structure, and possible different reaction mechanism .…”
Section: Iridium-based Water Oxidation Catalystsmentioning
confidence: 99%
“…Amorphous iridium oxides are regarded as more active but less stable catalysts for the acidic OER compared with crystalline rutile-phase iridium oxides. , Several methods have been developed to obtain amorphous iridium catalysts such as surface oxidation of iridium metal, , leaching of ions in iridium compounds such as SrIrO 3 , , incorporation of alkali metal ions into iridium oxide, light-driven decomposition, and anodic deposition from iridium-based organometallic precursors. The origin of the higher electrochemical activity of amorphous iridium oxides is attributed to several possible structural features, including electronic defects (O 2p hole states), flexible and disordered [IrO 6 ] octahedrons, cross-linked hollandite-like structure, and possible different reaction mechanism .…”
Section: Iridium-based Water Oxidation Catalystsmentioning
confidence: 99%
“…Compared to the HER process in the water electrolyzers, the pathway for the OER reaction that includes a four-electron process is slower and more complicated. ,, Therefore, high OER activity is a vital process to improve the efficiency of PEMWE. Although OER mechanisms have not been fully understood, it is shown that structural features of catalysts, for instance, morphology and particle size, significantly influence the OER performance. , Furthermore, it is agreed that efficient transport of charge and mass would enormously affect the functionality of water electrolyzers.…”
Section: Introductionmentioning
confidence: 99%
“…Although OER mechanisms have not been fully understood, it is shown that structural features of catalysts, for instance, morphology and particle size, significantly influence the OER performance. 14,18 efficient transport of charge and mass would enormously affect the functionality of water electrolyzers. Among responsible loss phenomena in the OER mechanism, bubble coverage of the electrode dramatically contributes to the final efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…27 Despite these efforts, it is still necessary to further enhance the catalytic activity of most OER catalysts to reduce their energy consumption for commercial usage. 3,5,9,28–30 Industrial anodes such as Ir oxide 5,31 also have disadvantages of high cost, scarcity and unsatisfactory catalytic activity. 2,3,32,33 Although a-IrO x structured catalysts show relatively high OER activity, much more active catalysts are needed to meet energy requirements, 3,8,12 which is the major endeavour of the present study.…”
Section: Introductionmentioning
confidence: 99%